2020
DOI: 10.1038/s41570-020-00232-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of anisotropic nanoparticles with precisely defined dimensions

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(184 citation statements)
references
References 333 publications
(372 reference statements)
0
154
0
2
Order By: Relevance
“…[31][32][33][34][35] Among other interesting findings, they reported that while homochiral PLLA-PAA and PDLA-PAA BCPs independently form cylinders with crystalline cores in THF/H 2 O at 65 C, upon heating a 1:1 mixture of both BCPs in solution or a mixture of the respective cylinders under the same conditions, small stereocomplex spherical micelles are formed by a unimer-exchange process. 31 Apart from these characteristic examples, several more crystallizable polymers have been utilized for the formation of cylindrical/"fiber-like" micelles with crystalline cores and a detailed account can be found in the recent review of MacFarlane et al, 24 while an equally interesting review on the preparation of anisotropic nanoparticles, including cylindrical micelles, and their applications has been published lately by Pearce et al 36…”
Section: Cylindrical Micellesmentioning
confidence: 99%
“…[31][32][33][34][35] Among other interesting findings, they reported that while homochiral PLLA-PAA and PDLA-PAA BCPs independently form cylinders with crystalline cores in THF/H 2 O at 65 C, upon heating a 1:1 mixture of both BCPs in solution or a mixture of the respective cylinders under the same conditions, small stereocomplex spherical micelles are formed by a unimer-exchange process. 31 Apart from these characteristic examples, several more crystallizable polymers have been utilized for the formation of cylindrical/"fiber-like" micelles with crystalline cores and a detailed account can be found in the recent review of MacFarlane et al, 24 while an equally interesting review on the preparation of anisotropic nanoparticles, including cylindrical micelles, and their applications has been published lately by Pearce et al 36…”
Section: Cylindrical Micellesmentioning
confidence: 99%
“…101 One of the unmet challenges in SP design is represented by the use of anisotropic NPs as building blocks. Indeed, although several research groups have investigated self-organization of anisotropic NPs, 102 the development of 3D SPs bearing confined nanocavities is still limited and isotropic NPs remain the preferred building blocks for confined SPs synthesis. In principle, anisotropy could favor different self-organization modes, with anisotropic NPs interaction mimicking more closely directional bonds in molecules, allowing different NP orientations in the assembly pattern.…”
Section: Opportunities and Challenges Of Confined Space By Nanoparticmentioning
confidence: 99%
“…This article highlights the liquid cell development and its associated work with a focus on nonspherical nanoscale materials, including the growth and transformations of PtFe nanowires, 2 facet development of Pt nanocubes, 13,21 twodimensional (2D) nanosheet formation with three-dimensional (3D) nanoparticles as the intermediates, 14 reversible giant deformation of PbSe nanocrystals during superlattice transformations, 11 and Li dendrites formation. 4,22 Not only do these material systems have unique anisotropic properties, 23,24 they are also ideal systems for exploring nonequilibrium behaviors at the nanoscale, in which a small perturbation can drive them out of equilibrium. To this end, direct observations with high spatial and temporal resolution are necessary for yielding critical insights to a range of related questions.…”
Section: Haimei Zhengmentioning
confidence: 99%